A integração de práticas educacionais e sociais na sala de aula de lingua inglesa via gêneros digitais orais - Helen de Oliveira Faria (2016)
The conception of learning as a decentralizedphenomenon embraces the notion that knowledge acquisition occurs in any space, not only in instructional environments. For this reason, it is essential that teachers integrate their students social practices into the classroom, so that activities, content and tools from diverse contexts can influence and interrelate each other, aiming at meaningful learning. Thus, the objective of this research was to investigate the interconnection of pedagogical practices of an English language classroom with the socialpractices of its learners in order to develop oral skills via face to face and digital environments. After administering an initial questionnaire to the class, the 2nd year of a technical and technological Electrotechnical course of a federal public school, themes, technologies and social practices of the students were selected to inform the development of eight tasks. The questionnaire form was fulfilled both in the classroom and in virtual contexts. The tasks were accessed, shared and commented on an online environment, in order to expand the traditional classroom. In addition to the initial and final questionnaires, the data comprised the participant observation of the researcher, the researcher journals written during the development of the activities and statements of the students delivered after the end of each task. Data were analyzed in the light of the complexity theory, the ecological approach and the concept of learning community, which contributed to the vision of learning through interaction, participation and collaboration in a complex perspective. The research results show the overcoming of face to face teaching and learning challenges of oral skills, the great engagement of the students during the classes motivated by their identification with